The Use of Cryopreserved Umbilical Tissue as an Adjunctive Therapy in Immediate Breast-Reconstruction Patients at High Risk for Wound-Healing Complications: Case-Report Series and Preliminary Results - Kyle M. Ockerman; Nhan Trieu; Sabrina H. Han; Markos Mardourian; Lisa Spiguel; Kalyan Dadireddy; Sarah Sorice Virk (Surgical Techniques Development)
Introduction: Mastectomy skin necrosis (MSN) is a common complication occurring in up to 50% of patients. In patients with risk factors for poor wound healing such as immunosuppression, prior radiotherapy (XRT), and high body mass index (BMI > 30.0), this number is even higher. MSN can lead to infection, loss of reconstruction, poorer aesthetics, and most ominously, delay in adjuvant cancer therapy. Instead of forgoing reconstruction in these patients, adjunctive therapies to optimize wound healing are necessary. The purpose of this study is to introduce the use of cryopreserved umbilical tissue (vCUT) as an adjunct therapy for high-risk-wound-healing immediate breast reconstruction (IBR) patients. Methods: All patients who underwent breast reconstruction with vCUT as an adjunctive therapy were identified and retrospectively analyzed. Results: Seven patients who underwent breast reconstruction with vCUT placement were identified. These patients had risk factors for delayed healing, such as obesity, immunosuppression, and/or prior XRT. The mean post-operative follow-up was 252 days (range 183–287). Four out of seven patients demonstrated post-operative complications: two out of seven developed seromas, two out of seven developed wound dehiscence, two out of seven developed infection, two out of seven developed MSN, and two out of seven lost their reconstruction. Conclusion: As undergoing IBR leads to improved mental health and superior aesthetic outcomes, efforts to expand current indications for safe IBR to traditionally poorer reconstructive candidates are imperative. The results of this case series demonstrate vCUT as a promising novel adjunctive tool in the reconstructive surgeons’ armamentarium in managing the less ideal reconstructive breast candidate.